Metagenomic Analysis of Human Diarrhea: Viral Detection and Discovery - Finkbeiner, S.R.; Allred, A.F.; Tarr, P.I.; Klein, E.J.; Kirkwood, C.D.; Wang, D.
Worldwide, approximately 1.8 million children die from diarrhea annually, and millions more suffer multiple episodes of nonfatal diarrhea. On average, in up to 40